Dectin-1 Promotes Type I and III Interferon Expression to Support Optimal Antifungal Immunity in the Lung - Dutta, Orchi; Espinosa, Vanessa; Wang, Keyi; Avina, Samantha; Rivera, Amariliz (Frontiers in Cellular and Infection Microbiology, 2020)
Pulmonary infections with Aspergillus fumigatus (Af) are a significant cause of invasive fungal disease and lead to high morbidity and mortality in diverse populations throughout the world. Currently available antifungal drugs are often ineffective, thus contributing to unacceptably high mortality rates in patients suffering from invasive fungal infections. The use of cytokines as adjunctive immune therapies holds the promise of significantly improving patient outcomes in the future. In recent studies, we identified an essential role for type I and III interferons as regulators of optimal antifungal responses by pulmonary neutrophils during infection with Af. Although various membrane and cytosolic nucleic acid sensors are known to regulate interferon production in response to viruses, the pathways that regulate the production of these cytokines during fungal infection remain uncovered. In the current study, we demonstrate that dectin-1-mediated recognition of β-glucan on the cell wall of the clinically relevant fungal pathogen Aspergillus fumigatus promotes the activation of a protective cascade of type I and III interferon expression. We further demonstrate that exogenous administration of type I and III interferons can rescue inadequate antifungal responses in dectin-1-/- mice, suggesting the potential therapeutic benefit of these cytokines as activators of antifungal defense in the context of innate defects.